THE EFFECT OF KEGEL EXERCISE ON URINARY INCONTINENCE IN THE ELDERLY AT SABAI NAN ALUIH TRESNA WERDHA SOCIAL HOME SICINCIN - SAVITRI, SILVIA; DORA, MECHI SILVIA; RAHMIWATI, RAHMIWATI (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Ageing is a natural process that can cause deterioration of physiological functions, including urinary incontinence, which is the inability to control urine output in the elderly. This problem not only affects physical health, but also social and psychological. One effective non-pharmacological method to treat urinary incontinence is Kegel exercises. Kegel exercises can strengthen the pelvic floor muscles or pubococcygeal muscles so as to strengthen the urinary tract muscles. This study aims to determine the effect of Kegel exercises on urinary incontinence in the elderly at the Tresna Werdha Sabai Nan Aluih Sicincin Social Home in 2024. This study uses quantitative methods with a Quasi experimental design without a control group. A total of 16 respondents were selected using purposive sampling technique. Before Kegel exercises, 56.3% of respondents experienced severe urinary incontinence. After Kegel exercises, the results showed that 68.8% of respondents experienced moderate urinary incontinence. Analysis using the Wilcoxon statistical test resulted in a p value = 0.001 (p < 0.05), indicating a significant effect of Kegel exercises on reducing urinary incontinence. The conclusion of this study is that Kegel exercises can significantly improve the condition of urinary incontinence in the elderly, so it can be used as an effective alternative non-pharmacological intervention in the management of urinary incontinence problems in the elderly.